2022
DOI: 10.1186/s10194-022-01441-9
|View full text |Cite
|
Sign up to set email alerts
|

Repeated inflammatory dural stimulation-induced cephalic allodynia causes alteration of gut microbial composition in rats

Abstract: Background Gut microbial dysbiosis and gut-brain axis dysfunction have been implicated in the pathophysiology of migraine. However, it is unclear whether migraine-related cephalic allodynia could induce the alteration of gut microbial composition. Methods A classic migraine rat model was established by repeated dural infusions of inflammatory soup (IS). Periorbital mechanical threshold and nociception-related behaviors were used to evaluate IS-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…The results showed that compared with the untreated mice, the head and face hyperalgesia of the mice in the SCFAs treatment group was reversed, the mast cell infiltration and inflammatory reaction in the intestine were significantly reduced, and the intestinal wall permeability was improved [7,18] . A recent research result of our research group also shows that in the IS-induced chronic migraine rat model, intestinal microbiota and tryptophan metabolism pathway will also be affected, and the disorder of intestinal microbiota and metabolism has also been corrected to some extent after the use of drugs to treat migraine [19] . At the same time, intestinal microorganisms can also enhance the stimulation of ECCs by improving the utilization of tryptophan [10] .…”
Section: Resultsmentioning
confidence: 91%
“…The results showed that compared with the untreated mice, the head and face hyperalgesia of the mice in the SCFAs treatment group was reversed, the mast cell infiltration and inflammatory reaction in the intestine were significantly reduced, and the intestinal wall permeability was improved [7,18] . A recent research result of our research group also shows that in the IS-induced chronic migraine rat model, intestinal microbiota and tryptophan metabolism pathway will also be affected, and the disorder of intestinal microbiota and metabolism has also been corrected to some extent after the use of drugs to treat migraine [19] . At the same time, intestinal microorganisms can also enhance the stimulation of ECCs by improving the utilization of tryptophan [10] .…”
Section: Resultsmentioning
confidence: 91%
“…Some observational studies have reported a relationship between gut microbiota and migraine ( Chen et al, 2019 ; Georgescu et al, 2019 ; Geisler et al, 2021 ; Kopchak et al, 2022 ; Kopchak and Hrytsenko, 2022 ; Liu et al, 2022 ; Miao et al, 2022 ; Bai et al, 2023 ; Yong et al, 2023 ). In the present study, the genus LachnospiraceaeUCG001 , which had not previously been identified, was discovered to be a risk factor for migraine for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…Headache may also lead to the occurrence of dysbiosis. Miao and his colleagues have reported that headache due to meningitis could lead to dysbiosis in gut, and they think that inflammatory dural stimulation-induced cephalic headahce causes the alterations of gut microbiota profile and microbial metabolic pathways [ 34 ]. However, these studies cannot provide the causal association between dysbiosis of gut microbiota and migraine.…”
Section: Discussionmentioning
confidence: 99%